Group Theory analysis and formulation in rationalizing the crystallographic point groups - Mohd Idrus Nor (Universiti Pendidikan Sultan Idris, 2009)
Group Theory analysis and formulation in rationalizing the crystallographic point groups by Mohd Idrus Nor